Assessment of toxic trace metals emitted from industrial sources in East of Turkey - Avci, Halim; Akdeniz, Ismail; Yaman, Mehmet (Asian Journal of Chemistry, 2008)
In this study, four-trace metals including nickel, copper, manganese and zinc and as a major element iron were determined in solid samples taken around industrial regions including thermoelectric power plant, copper mining plant, ferrochrome plant, cement factory and other probable polluting sources in east of Turkey. The solid samples were collected from 29 different points and trace metals were extracted from matrix by aqua regia by using wet ashing method. Trace metals were determined by flame atomic absorption spectrometry (FAAS). The metal concentrations in soils were found in ranging as mg/kg; 11-89 for Ni, 6-35 for Cu, 77-893 for Mn, 58-122 for Zn and 10343-32226 for Fe and in industrial samples were found to be in ranges as mg/kg; 25-1942 for Ni, < detection limit (DL) of 4.5 ng/mL - >4000 for Cu, 22-768 for Mn, 14-6580 for Zn and 2300- >80000 for Fe.
Keywords: toxic trace elements; soils; bottom and fly ash; power plants; industrial pollution